Aplicação e caracterização de poucas camadas de dissulfeto de molibidênio na produção de transistores de efeito de campo - Juliana Alves Martins (2012)
In this work we investigate the fabrication of electronic devices based on a few layers of Molybdenum Disulfide (MoS2). To achieve this goal we have performed a study that involved the preparation and deposition of the crystal on the silicon substrate (covered with a layer of silicon oxide), its identification and characterization, and the final production of field effect transistors. The identification of the number of layers of MoS2 was performed mainly using four different techniques, namely: optical microscopy, atomic force microscopy (AFM), Raman and photoluminescence spectroscopy. After the identification of the number of layers and the characterization of the samples, field effect transistors were built using few-layers of MoS2 as the active channel. The device fabrication was performed using processes of electron beam lithography and optical lithography. In the search for ohmic contacts, a systematic study was carried out using different metals (Cr / Au, Ti / Au and Au). Among these, only the contact made with pure gold was shown to display ohmic characteristics. Thus, the latter was chosen for the fabrication of transistors devices where the field effect (through the application of the back gate voltage) modulates the conduction of the MoS2 channel. By performing the transconductance measurements, we were able to determine important properties of MoS2 such as its n-type doping, mobility and carrier density.